Analisis Stakeholder dalam Penanggulangan HIV dan AIDS di Kabupaten Grobogan - Ratna Kusumasari Purbani; Yodi Mahendradhata; Yanri Wijayanti Subronto (Jurnal Kebijakan Kesehatan Indonesia, 2019)
HIV-AIDS is one of the world's health problems. Grobogan regency is one of the districts in Central Java with HIV number 4 and the discovery of new cases of HIV-AIDS number 3 in Central Java by 2015. Until 2017, HIV-AIDS cases are still fluctuating and tend to increase. Efforts were made to garner support and political commitment from the Grobogan Government and other stakeholders. The continuity of the program depends on political commitment and stakeholder policy support in the region. Conducting stakeholder analysis becomes important for the development of future strategic HIV / AIDS prevention plans. Objective this research to describe how local government strategic planning in HIV and AIDS prevention in Grobogan District. This research is descriptive research with qualitative approach. There were 20 informants in the study: Executive and Legislative officials, HIV / AIDS Caring NGO, VCT Clinic, community of PLWHA. The data was collected by observation, in-depth interview, and document review. Local government strategic planning on HIV / AIDS prevention efforts is still in the form of policy agenda and exit strategy. Although all stakeholders agree and support HIV / AIDS prevention efforts, stakeholder involvement in the formulation of policies and programs is lacking. Coordination of health offices with other stakeholders is also not working well, so the program is not integrated. The health department advocacy to local leaders is still weak. Health workers began to be evaluated for their performance, especially at sub-district level. Proposed alternatives to HIV / AIDS prevention budget from village funds. Unintegrated HIV / AIDS prevention efforts by stakeholders show weak communication and coordinative functioning. This problem is mainly caused by the key personnel dealing with reshuffle including the head of the health office in addition to the new bupati also not fully understand the case of HIV-AIDS that occurred.